Influence Of Work Health Safety And Work Environment On Employee Satisfaction At PT. Indonesia Toray Synthetics - Giovanni Savio; Pujiarti Pujiarti; Fidellis Wato Tholok; Suhendar Janamarta (Fakultas Bisnis, 2020)
The results of processing the data obtained by multiple linear regression equation Y = 2,937 + 0,485X1 + 0,415X2, meaning that any increase or decrease in the occupational health safety variables by 1 point, then the level of job satisfaction of employees at PT. Indonesia Toray Synthetics will increase or decrease by 0.485 and any increase or decrease in the working environment variable by 1 point, then the level of job satisfaction of employees at PT. Indonesia Toray Synthetics would have increased or decreased by 0.415. In addition, the authors also calculate the influence between variables. Correlation between occupational health safety and job satisfaction is equal to 0.661, and the correlation between the work environment and job satisfaction of employees amounted to 0.613. It can be concluded that the relationship between these three variables is strong and has a positive influence. From the test results F, model 1 obtained value of 76.187 with a significance level of 0.000, and model 2 obtained value of 50.841 with a significance level of 0.000. The results are greater than the value of which amounted to 3.09 Ftabel, then H0 is rejected and Ha accepted. While the results of the t test can be calculated at 5.205 occupational health safety and working environment t value is 3.845. Both values ​​are greater than the value that is equal to 1.98447 ttable. That is, there is a significant relationship between occupational health and environmental safety work on employee job satisfaction.